POSITIVE AND NEGATIVE ASPECTS OF HUNGARY'S INDUSTRIAL TRANSFORMATION IN THE CONDITIONS OF EUROPEAN INTEGRATION - Oleg Dmitrievich Protsenko; Mihail N. Dudin; Nikolaj V. Lyasnikov (Модернизация, инновация, развитие, 2016)
This article describes the main historical trends, formed the preconditions for the transformation of the industry of Hungary, and studied the features of the development of the industrial sector in terms of European integration. Within the article highlighted the positive and negative aspects of the transformation of Hungarian industry in the context of European integration and, in addition, formulated the basic directions of the further economic and industrial development of the country. Methodology. In this article, based on the methods of historical and retrospective economic and statistical analysis outlines the main trends that determine the development of Hungarian industry in the context of European integration. With the use of the comparative analytical method, developed in the works of MV Panova [3] ranging of regions of the country on the level of economic development activity. The basis of the analytical method laid the ratio of the economically and industrially active regions on areas of the country to the total population of these regions based on key socio-economic indicators: population, economic indicators, the number of industrial enterprises, agriculture and service sectors, the investment attractiveness of regions. On the basis of previously made predictions (see. Works VL Martynov [4] and R. Brunet [5]) formed the main points that determine the further industrial and economic development of Hungary in the framework of European integration.